A estrutura de capital, o capital de curto prazo e a rentabilidade das empresas: um estudo empírico com empresas brasileiras - Fialho, Josely Lopes (2010)
The main objective of this dissertation is to verify if there is any relationship between profitability and the composition of short-term debt used by non-financial Brazilian companies traded in its structure. We used the relationship between net income and total assets to measure the return for the company. More specifically, this study examines the hypothesis that the return for the company, on average, not be equal, when considering its size and level of short-term debt. This reason tests were performed in two stages with the same sample: i) a sample divided into three groups by size - the average total active attribute of the analyzed period and ii) another sample of two groups separated by CCL positive and negative. Both analyses were performed considering the companies traded on the BOVESPA and belonging to the segment New Market of Corporate Governance - NMGC, for the period between 2003 and 2008. The choice of NMCG companies was based on their commitment of improving the quality of information to be provided to their stakeholders. We used the Spearman correlation test of hypothesis and nonparametric Mann-Whitney and Kruskal-Wallis were used for the average population, by the observation of the significance of calculating averages for samples and groups. The results show that the comparison between groups of samples, both at the first stage as in the second, the profitability of companies presents little variation, confirming the null hypothesis. However, tests show that there is no indication that the quality of debt is correlated with the profitability of enterprises, even modest. Further studies are proposed in order to better highlight the problem presented in this dissertation